Experimental corruption research in Germany: the lab studies - Fürstenberg, Alexander (Organizational crime, 2023)
Corrupt decisions in organizations may be influenced by the informal rules of the organizational culture. Therefore, hypotheses on influencing corrupt decisions due to competitive pressure, hierarchical pressure, the rationalizing and legitimacy of corporate social responsibility, organization-specific socialization, and gender are examined. By using laboratory experiments with students in Germany, these organizational-cultural conditions are tested for corrupt decisions either for personal or organizational advantages. The results support an analytical separation between individual and organizational corruption as well as the corruption-decreasing effects of competitive pressure, and the rationalizing and legitimacy of corporate social responsibility in our population.
Gesehen am 11.05.2023